Performance evaluation of Iranian valid scientific journals in the field of accounting and finance - Batoul Zargar; Mahdi Mohammadi (مجله علم‌سنجی کاسپین, 2018)
Background and aim: With increasing competition in the scientific society, attention to the quality of journals has enhanced and different methods are used to evaluate the journals. Therefore, the aim of this study was to find a comprehensive view on the status of the performance of the valid journals in the field of accounting and finance in Iran by gathering different evaluation criteria. Material and methods: This evaluative study was conducted using a scientometric method. Evaluation criteria consisting 14 components were prepared based on studies performed in this field, data on various components were collected by referring to the website of the journals and databases, and finally, these data were analyzed using Excel. The statistical population was 18 and 9 accounting and financial journals, respectively. Findings: The findings showed that 66.6% of journals were published by State universities and 33.4% by other centers. According to the State Journal database, 3 journals were ranked A and the others B and C. No journal was ranked A+. The mean of immediacy index and impact factor were 0.018 and 0.253 in the accounting journals and 0.015 and 0.123 in the financial journals, respectively. Only one journal was indexed in 6 national and 4 international databases. Totally, 18% of the journals were indexed in 80% of these databases and the others in lower ranks. In summary, two journals of "Financial Accounting Research" and "Financial Knowledge of Securities Analysis" were ranked first in this field. Conclusion: Averagely, accounting journals have higher impact factor and cumulative citations compared with financial ones. It is necessary to pay attention to the quality of articles in financial journals and indexing in valid databases in accounting journals.